Export Competitiveness of Indonesian Coffee In Germany - Fadhlan Zuhdi; Rachmiwati Yusuf (HABITAT, 2021)
Coffee has been one of the mainstay products for Indonesia's exports to Germany since the last time and the frequency continues to increase. This reflects that Germany's need for coffee continues to grow. This study aims to measure the position of Indonesia's coffee export competitiveness in Germany. The method used in this research are Revealed Comparative Advantage (RCA) and Constant Market Share (CMS). The results showed that Indonesia's coffee exports were not competitive in Germany and had a downward trend. The export performance of Indonesian coffee in Germany also shows a downward trend in each period. Several things that need to be improved so that the competitiveness and performance of Indonesia's exports can increase is by disseminating information regarding the use of cultivation technology to increase the productivity of Indonesian coffee.